Nilai – Nilai Akhlak Terhadap Allah SWT dalam Antologi Puisi Sang Pencipta, Cinta dan Renungan Kehidupan karya Anik Puji Rahayu - Yulianti, Elsa Dwi; Israhayu, Eko Sri (Ruang Kata, 2023)
This research examines the relation to moral values ??towards Allah SWT in the anthology of the poem The Creator, Love and Reflection on Life by Anik Puji Rahayu. This research is included in qualitative research. This study uses data in the form of words and sentences related to moral values ??towards Allah SWT. The source of data in this study is the anthology of poetry by Anik Puji Rahayu entitled (Happy Peace in the Soul), (Rain Brings Blessings), (Ahead of Ramadhan Arrives), (Blessings of Life), (Grateful), (Patience), (Message of the Bayu ), and (Power and Conscience). Data collection techniques in this study used reading and note-taking techniques. The reading technique is carried out by carefully reading the anthology of poetry by Anik Puji Rahayu by considering moral values. Then the note-taking technique is carried out by tagging or recording data related to moral values ??in the anthology of poetry by Anik Puji Rahayu. The data validation technique used in this study is theory triangulation and data sources. The data analysis technique used is data reduction, data presentation, and drawing conclusions. This poetry anthology of The Creator, Love and Reflection on Life is a poetry anthology which contains many moral values ??for Allah SWT in the form of piety, sincerity, trust and gratitude which are sourced from his life experiences. Piety can be interpreted to follow all His commands and stay away from all His prohibitions. Ikhlas is a charitable act solely to expect the pleasure of Allah SWT. Tawakal is surrender, believing in Allah that work, soul mate and death are His will. Then gratitude is a feeling of gratitude to Allah for all the blessings given to his servant. The results of the research data found are related to moral values ??towards Allah SWT in the poetry anthology of The Creator, Love and Reflection on Life, namely the attitude of piety has 4 data, the attitude of sincerity has 2 data, the attitude of trust has 5 data and the attitude of gratitude has 3 data. Keywords: poetry anthology, religion, morals.